Analisis Pengaruh Tenaga Kerja, Luas Lahan Dan Pupuk Terhadap Ketersediaan Pangan Kabupaten/Kota Di Provinsi - Yuliyanto, Eko, Didit Purnomo, SE., M.Si (2017)
The research titled "analysis the effect of labor, land and fertilizer to the availability of food regency/city in central java". The purpose of this study was to determine whether the variabel labor, land and fertilizer affect the availability of food regency/city in central java. The research was conducted by using linear regression analysis with Ordinary Least Square method (OLS). The variable in this study is the variable of labor, land, fertilizer and availability food. Based on the results of the analysis showed that the variables of labor does not have a significant influence on the availability of food, variable land area has a significant influence towards the availability of food at the level α = 0,10 with a coefficient of 0,0000 and variable fertilizer has a significant influence on the availability of food on the level α = 0,10 with a coefficient of 0,0846.